Marketing and Socio-Psychological Factors Influencing Consumption Bakery Product in Thailand - Pornnapa Thanapotivirat; Tharnupat Jithpakdeepornrat (Studies in Business and Economics, 2022)
The aim of research was to study consumer buying behavior for bakery products in Thailand and to investigated the effect of marketing and socio-psychogical factor on the consumption bakery product in Thailand. Population of the research was the consumer who consume the barkery within 400 samples. The researchers obtained questionaire in Pathumwan District, Sathorn District, Silom District, Bang Rak District, which is an economic district and has a variety of snack shops and bakery shops. The data analyze was applied by percentage, mean, and standard deviation. To test the research hypotheses, Multiple Regression statistics was used. The results showed that marketing and socio-psychogical factor influenced consumer behaviors for bakery products in Thailand within significant at the 0.05 level.